(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Linear stability of a rotating fluid saturated porous medium heated from below is studied when the fluid and solid phases are not in local thermal equilibrium. The Darcy model which includes Coriolis term with anisotropy permeability is employed as a momentum equation. The critical Rayleigh number for the onset of convection using linear stability analysis is found numerically as a function of mechanical anisotropy parameters, interphase heat transfer coefficient, aspect ratio and Taylor number. It is found that a small interphase heat transfer coefficient has significant effect on the stability of the system. The rotation inhibits the onset convection. The effect of porosity modified conductivity ratio, diffusivity ratio, interphase heat transfer coefficient on the stability of the system is investigated.